A Hop-Count Analysis Scheme for Avoiding Wormhole Attacks in MANET - Chi-Sung Laih; Shang-Ming Jen; Wen-Chung Kuo (Sensors, 2009)
MANET, due to the nature of wireless transmission, has more security issues compared to wired environments. A specific type of attack, the Wormhole attack does not require exploiting any nodes in the network and can interfere with the route establishment process. Instead of detecting wormholes from the role of administrators as in previous methods, we implement a new protocol, MHA, using a hop-count analysis from the viewpoint of users without any special environment assumptions. We also discuss previous works which require the role of administrator and their reliance on impractical assumptions, thus showing the advantages of MHA.